2004
DOI: 10.1783/147118904322995465
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of married individuals towards oral contraceptives: a qualitative study in Istanbul, Turkey

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Similar findings were established in a study that found high rates of discontinuation among rural Kenyan women living in discordant partnerships [26]. Studies conducted to examine factors influencing contraceptive adherence have concluded that beliefs, attitudes, and daily life activities affect consistent and correct contraceptive use [27][28][29][30]. However, little is known about rates of discontinuation and contraceptive adherence among Ugandan women.…”
Section: Introductionsupporting
confidence: 66%
“…Similar findings were established in a study that found high rates of discontinuation among rural Kenyan women living in discordant partnerships [26]. Studies conducted to examine factors influencing contraceptive adherence have concluded that beliefs, attitudes, and daily life activities affect consistent and correct contraceptive use [27][28][29][30]. However, little is known about rates of discontinuation and contraceptive adherence among Ugandan women.…”
Section: Introductionsupporting
confidence: 66%
“…This findings are consistent with reports in other studies on influence of socio-cultural factors on choice and uptake of modern FP (14,16,18,20,21,(26)(27)(28)(29)(30)(31)(32), and confirm the need for having constructive partner discussions as a way of encouraging contraception uptake. However, they contrast with those in turkey where cultural beliefs greatly influenced use of contraception (19).…”
Section: Discussionmentioning
confidence: 90%
“…Low usage has been widely attributed to the negative attitude towards this form of contraception. Specifically, approval/ disapproval of the modern methods by self and partner (13,(16)(17)(18)(19)(20), fear of harmful effects on health (12, 13,17,19,21,22), and low levels of education (13,17,23) have been identified to influence use of modern FP methods in Africa, Asia and other parts around the world. This observation suggests that both the women and their partners lack the right information that will aid decision making on use, an argument supported by evidence from related studies that showed increasing knowledge on the methods can result to higher utilization (24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that married men participating in this research had accurate information about this issue. Studies indicated that men were interested in and concerned about adverse effects of family planning methods [16, 17]. In addition, these adverse effects were specified as reasons for quitting IUD method [2].…”
Section: Discussionmentioning
confidence: 99%